Factor Analysis of Menstrual Duration, Level of Knowledge, and Compliance with the Consumption of Blood Supplement Tablets on the Prevalence of Anemia in Adolescents with Prostate - Nita Dwi Astikasari; Candra Wahyuni; Tety Ripursari; Devi Mandasari (Universitas STRADA Indonesia, 2025)
Background: Anemia is a major health concern among adolescents, particularly females, and is closely linked to prolonged menstrual bleeding, insufficient knowledge about anemia, and poor compliance with iron supplementation programs. These factors contribute significantly to the high prevalence of anemia, which can lead to decreased physical performance, impaired cognitive function, and reproductive health complications in later life. Purpose: This study aims to analyze the relationship between menstrual duration, level of knowledge about anemia, and compliance with the consumption of blood supplement tablets on the prevalence of anemia in adolescents. Methods: The research uses quantitative methods with a correlational analytical research design with a cross sectional approach. The population and sample in this research were 30 female students. Bivariate data analysis used the chi-square test with the help of SPSS 26. Results: The research results show that there is a relationship between Menstrual Length and Anemia in young women at SMA Negri 1 Kediri, (p value=0.023), there is a relationship between Knowledge and Anemia in young wo/men at SMA Negri 1 Kediri (p value = 0.042) and there is a relationship between compliance with blood supplement consumption and anemia in young women at SMA Negri 1 Kediri x (p value=0.023). Conclusion: The results of this study indicate that menstrual duration, level of knowledge about anemia, and compliance with the consumption of iron supplement tablets are significant factors influencing the prevalence of anemia among adolescent girls. Among these, compliance with iron tablet consumption emerged as the most dominant factor, suggesting that behavioral aspects play a crucial role in anemia prevention. Additionally, limited knowledge about anemia and prolonged menstrual duration were also associated with a higher risk of anemia. These findings highlight the need for comprehensive health education programs that not only increase awareness about anemia but also promote consistent intake of iron supplements, particularly among adolescents. Effective interventions should prioritize improving knowledge and fostering positive health behaviors to reduce the incidence of anemia and support the overall well-being of young women.